Preliminary Multi-Physics Performance Analysis and Design Evaluation of UO2 Fuel for LBE-Cooled Subcritical Reactor of China Initiative Accelerator Driven System - Wang, Guan; Gu, Long; Yun, Di (Frontiers in Energy Research, 2021)
China initiative Accelerator Driven System (CiADS) and corresponding LBE-cooled subcritical reactor, as one of major national science and technology infrastructure projects, are undertaken by Institute of Modern Physics-Chinese Academy of Sciences (IMP-CAS). And at the first phase, UO2 fuels will be loaded in the subcritical core to test the coupling technology and achieve the long-term steady operation. The brief description of CiADS subcritical reactor, fuel assembly and fuel pin are presented here, and the multi-physics performance analysis and design evaluation of CiADS UO2 fuel are carried out by means of FUTURE code. FUTURE is a fuel performance analysis code to evaluate the synergy of the phenomena occurring in the fuel pin and their impact on the fuel design improvement for liquid metal fast reactor, which is developed jointly by IMP-CAS and Xi’an Jiaotong University (XJU). In this paper, FUTURE code is modified and updated focusing on CiADS fuel. Some of calculating and analysis functions are shut-down, while relocation and densification are added. Fission gas release is modified to be available in the low level of temperature and burnup. Results of the hottest fuel pin, mainly about the thermo-mechanical behaviors, are discussed concerning both fuel and cladding performance on the basis of indicative design limits. According to the preliminary design, the CiADS UO2 fuel exhibits a good performance and main parameters are far below the indicative limits. The FCMI is not very serious, and the permanent cladding strains and CDF are small and even negligible thanks to the low level of the temperature and corresponding stress. However, some critical issues may still exist, especially on LBE (Lead-bismuth Eutectic) corrosion in the entrance, where protective oxide layers are very thin from BoL to EoL. The modelling is useful for giving feedback to the conceptual design of the CiADS LBE-cooled subcritical reactor and the update of FUTURE code.